Modeling and fabrication of CMOS surface acoustic wave resonators - Nordin, Anis Nurashikin; Zaghloul, Mona E. (IEEE, 2007)
A fully integrated two-port surface acoustic wave (SAW) resonator, fabricated using a standard 0.6- m complementary metal–oxide semiconductor (CMOS) process is described in this paper. Only three micromachining processes, namely, reactive ion etching, zinc–oxide deposition, and wet etching, implemented subsequent to the standard process, are required to realize these resonators. Three design examples of these resonators are given to demonstrate the characteristics of these resonators at different operating frequencies. Experimental measurements of the S21 transmission characteristics were conducted on the fabricated resonators and they were found to have parallel resonant frequencies of 1.02 GHz, 941 MHz, and 605 MHz and quality (Q) factors of 44, 86, and 285, respectively. Based on these measurements and the fabrication layers of the device, an equivalent-circuit model tailored specifically for standard CMOS two-port resonators was developed. Finite-element modeling of the SAW resonators was performed to verify the measured series resonant frequency. Comparison between the developed model and measurement characteristics was also presented. Improvement in factor was observed when reflector height was increased.